Bancalimentos: the experience of turning wastes into currency for the territorial sustainable development - Tovar Cortès, Luisa Fernanda; Guevara Castañeda, Diego (Cooperativismo & Desarrollo, 2021)
Bancalimentos is a social innovation that values waste by assigning points that can be exchanged for food or cleaning products. The article examines how, in the experience of Bancalimentos, waste becomes a means of change, but also a social and environmental articulator for territorial sustainable development in the munici-pality of Fómeque (Cundinamarca).Through a methodological approach based on participation-action and dialogue of knowledge that used qua-litative and quantitative tools to cover the experience in detail, a fieldwork was carried out between April 2019 and January 2020. The co-creation process between the gseid research group and Bancalimentos projected reflections that seek to contribute to the understanding of popular financing initiatives and the complexity of currency as a social relationship from which waste is analyzed as a means of change and a driving force of social relations.In addition, the strategies that Bancalimentos has used in terms of acceptability, sustainability and replicability that can be considered for future initiatives are researched. The final considerations outline the challenges of Bancalimentos and the need for strong institutional support to enhance this type of social innovation.